Dowling-Degos disease and hidradenitis suppurativa: Co occurrence or association? - Choudhary, Sanjiv V. (Medknow Publications & Media Pvt Ltd, 2013)
A 44 year old female patient presented with multiple, painful, relapsing, nodules, plaques with sinuses discharging pus and scars in apocrine gland bearing region since past 17 years. These lesions were clinically and histopathologically suggestive of hidradenitis suppurativa. Our patient was not aware about the flexural pigmentary lesions, comedones and pitted scars which were also clinically and histopathologically suggestive of Dowling–Degos disease. We are reporting a rare interesting association of Dowling Degos disease and hidradenitis suppurativa which is not reported in Indian literature till date.